Clinical outcomes and dialysate calcium concentrations in Chinese patients on maintenance hemodialysis: a retrospective cohort study - Yurong Pan; Yunhan He; Yunyan Murong; Juan Xu; Wenqin Yang; Wenyan Guo; Jianlin Jian; Haiwen An; Yanlin Li; Qingxiu Huang; Linna Liu (Renal Failure, 2025)
Background The appropriate concentration of dialysate calcium (DCa) for maintenance hemodialysis (MHD) patients remains a subject of ongoing debate. The relationship between DCa concentration and patient outcomes is not yet well established. This study aimed to evaluate the impact of DCa concentration on mortality and major adverse cardiovascular and cerebrovascular events (MACCEs) in Chinese patients undergoing MHD.Methods A retrospective matched cohort study was conducted, analyzing data from hemodialysis (HD) patients at our center over the past five years. Each patient in the low DCa group was matched with a counterpart from the mid DCa group. Outcomes, including mortality, MACCE rates, fracture rates, and hospitalization rates, were compared between the two groups.Results The study included 924 MHD patients, of whom 101 low DCa patients were matched with 101 mid DCa patients. In the matched-pair analysis, no significant difference was observed in all-cause mortality between the low DCa and mid DCa groups (3.5/100 vs. 4.7/100 patient-years). However, the low DCa group exhibited lower cumulative rates of MACCEs, hospitalization, and fracture incidence compared with the mid DCa group (7.3/100 vs. 20.7/100 patient-years, 21.5/100 vs. 34/100 patient-years, and 1.6/100 vs. 3.9/100 patient-years, respectively). In addition, the adjusted hazard ratio (HR) for the occurrence of first MACCE in the low DCa group compared with the mid DCa group was 0.47 (95% CI: 0.24–0.91).Conclusions These findings suggest that low DCa concentrations are associated with reduced rates of MACCEs, hospitalization, and cumulative fracture incidence in MHD patients relative to mid DCa concentrations.